Rolled tobacco smoke in the rural area of şanliurfa - Yanık, Medaim; Gencer, Mehmet; Altındağ, Abdurrahman; Ceylan, Erkan; Keklik, Abdulbaki; Katı, Mahmut (Journal of Dependence, 2006)
Objective: There are numerous studies about smoking filter-tipped cigarettes in Turkey. However, there is only one study about smoking rolled tobacco according to our knowledge. Smoking rolled tobacco is common in Eastern and Southeastern Turkey. The purpose of this study was to investigate sociodemographic characteristics, smoking habits and dependence levels in people who smoke rolled tobacco in the rural area of Sanliurfa. Methods: This was study performed in a village in Siverek district of Sanliurfa. The village had a total population of 600. Two hundred ninety-nine subjects over 15 years of age were recruited in the study. Fagerstrom Tolerance Scale and a questionnaire about smoking rolled tobacco which were prepared by research team were applied to all subjects. Results: This study included 299 subjects (55.5% male, 44.5% female). The mean age of subjects was 35.7 ± 15.8 years old. Thirty-eight percent of subjects were illiterate. Fourty-seven percent of subjects (n=141) had used tobacco at least one period of their lifetime. Thirty-eight percent of subjects (n=116) were currently smoking tobacco. Ninety-three percent of subjects were smoking rolled tobacco, while only 7% were smoking cigarettes. 58.2% of subjects smoked more than 20 cigarettes a day. 13.6 % of subjects smoked more than 30 years, 84.4% smoked tobacco without filter, 84.4% smoked without a cigarette holder. Whereas 21% of subjects collect rolled tobacco in a cigarette case, others roll tobacco for each smoke. 17% of subjects sometimes smoke filter-tipped cigarettes besides rolled tobacco. 81.7% of subjects had a family member who smoke rolled tobacco. The reason for smoking rolled tobacco was its low cost compared to filter-tipped cigarettes for 49.1% of subjects. 87.5% of subjects thought that rolled tobacco was more harmful than filter-tipped cigarettes. The average score of Fagerstrom Tolerance Scale was 8.79±1.46 in the study group. These results suggested that 79.6% of subjects who smoke rolled tobacco had physical dependence on nicotine. Conclusion: Rolled tobacco smoking is the most common form of tobacco use in the rural area of Sanliurfa. Traditional usage and the low cost of rolled tobacco are the important factors which determine smoking rolled tobacco in Sanliurfa.